A long-term survivor of recurrent esophagogastric junction adenocarcinoma treated with multidisciplinary therapy: a case report - Takako Tanaka; Takaaki Arigami; Yoshikazu Uenosono; Shigehiro Yanagita; Daisuke Matsushita; Keishi Okubo; Takashi Kijima; Yasuto Uchikado; Yoshiaki Kita; Shinichiro Mori; Ken Sasaki; Itaru Omoto; et al. (Surgical Case Reports)
Abstract Background Patients with esophagogastric junction cancer are increasing in Western and Eastern countries. Conversely, the clinical significance of surgical resection remains controversial in these patients. We report a long-term survivor of recurrent esophagogastric junction adenocarcinoma who underwent constructive multimodal therapy, including surgical resection. Case presentation A 51-year-old man underwent total gastrectomy for esophagogastric junction adenocarcinoma in 2009. In June 2010, computed tomography (CT) indicated a lung nodule and we partially resected the right lower lung. It was pathologically diagnosed as distant metastasis from esophagogastric junction cancer. After lung resection, he received adjuvant chemotherapy with S-1 for 1 year. In September 2014, CT demonstrated a swelling of the upper mediastinal lymph node with abnormal uptake on fluorine-18 fluorodeoxyglucose positron emission tomography. We performed an ultrasonography-guided needle biopsy, and he was diagnosed with lymph nodal recurrence of esophagogastric junction adenocarcinoma by pathological examination and was subsequently treated with capecitabine plus cisplatin plus trastuzumab. Since CT showed a reduction in the metastatic upper mediastinal lymph node after chemotherapy, he underwent upper mediastinal lymphadenectomy in April 2015. Following surgery, we provided radiation therapy to the upper mediastinum and chemotherapy with S-1. At the last report, the patient was alive for 8 years and 3 months since the first surgery. Conclusions This case report shows the clinical benefit of constructive multimodal therapy for recurrent esophagogastric junction adenocarcinoma.